Application of The Project Based Learning Model Based on Honai Literacy and Critical Thinking Skills to The Papuan Student Community in Surabaya - Chanthoeurn Dock; Yanius Kogoya (Universitas Negeri Surabaya, 2023)
This research aims to determine the application of the Honai Literacy-based PjBL model and the critical thinking skills of the Papuan student community in Surabaya. This research uses descriptive analysis research type with a sample of 12, in a population of 31 students from different campuses in Surabaya. The research results show that the Honai literacy that was designed, if seen from the average coefficient of Honai learning before and after, is 7.25. This score is the average value of the before and after treatment. To say whether the value of 7.25 is meaningful or not depends on the results of the T test. The T results show a value of around 2.7 with a P-value of 0.021. 90% can be said to be a significant difference, of course 0.021<0.05, so there is a significant difference in Honai literacy-based learning in Surabaya